Environmental policy in climate change law with smart regulation - Muhammad Asmaul Bainto (Journal of Earth Kingdom, 2026)
Background: In Indonesia, environmental law plays an important role in addressing climate change. This study aims to explore the direction of environmental legal politics on climate change in Indonesia by considering the principles of sustainable development and applying the theoretical approach of smart regulation. Methods: This study employs normative legal research using statutory, historical, and conceptual approaches to examine the coherence of existing legal norms, complemented by a socio-legal method to assess how these norms are enforced and complied with in practice, particularly in relation to smart regulation as an emerging approach in Indonesian environmental law. Findings: Climate change policy consists of a range of targeted strategies and measures implemented by governments or the international community aimed at reducing global warming and addressing its effects. The results show that Indonesia’s climate change policies are developing toward recognizing the role of indigenous peoples and local communities as environmental protectors, in line with the commitment to reducing emissions. The implementation of economic instruments such as carbon trading and sustainability reporting is an important step forward in creating a more responsive and flexible policy mix in accordance with the principles of Smart Regulation. Conclusion: The main scientific contributions include the development of the theory of hybridization and localization of international law, the conceptualization of integrated policies based on carbon economic value (CEV), the reformulation of legal instruments through smart regulation theory, and the identification of legal gaps for cross-sectoral harmonization. Integrated legal hybridization and economic instruments are essential to transform fragmented environmental policies into a responsive, cross-sectoral framework. Novelty/Originality of this article: This study pioneers the application of Smart Regulation theory to Indonesian climate law by conceptualizing carbon economic value within localized indigenous governance.